MORPHOLOGICAL FEATURES OF CHANGES IN THE BRAIN TISSUE IN MILD CRANIOCEREBRAL INJURY (Archive of Conferences, 2020)
With head injuries received for reasons of various origins, the maintenance and support of the functional activity of the central nervous system is the main problem of practicing physicians. To study the mechanism of the occurrence of disorders, as well as to determine their compatibility with the vital functions of the body's systems, to predict the degree of risk to life, a comprehensive consideration of all links of pathogenetic disorders, including at the level of morphological changes, is necessary. With a mild degree of traumatic brain injury, changes in the body may not be pronounced, which complicates the diagnosis and selection of adequate therapy measures.